Molecular Evolutionary Analyses of Shiga toxin type 2 subunit A Gene in the Enterohemorrhagic Escherichia coli (EHEC) - Ryusuke Kimura; Hirokazu Kimura; Tatsuya Shirai; Yuriko Hayashi; Yuka Sato-Fujimoto; Wataru Kamitani; Akihide Ryo; Haruyoshi Tomita (Microorganisms, 2024)
To better understand the molecular genetics of the Shiga toxin type 2 subunit A gene (stx2A gene), we collected many subtypes of stx2A genes and performed detailed molecular evolutionary analyses of the gene. To achieve the aim of the study, we used several bioinformatics technologies, including time-scaled phylogenetic analyses, phylogenetic distance analyses, phylodynamics analyses, selective pressure analyses, and conformational epitope analyses. A time-scaled phylogeny showed that the common ancestor of the stx2A gene dated back to around 18,600 years ago. After that, the gene diverged into two major lineages (Lineage 1 and 2). Lineage 1 comprised the stx2a–2d subtypes, while Lineage 2 comprised the stx2e, 2g, 2h, and 2o subtypes. The evolutionary rates of the genes were relatively fast. Phylogenetic distances showed that the Lineage 2 strains had a wider genetic divergence than Lineage 1. Phylodynamics also indicated that the population size of the stx2A gene increased after the 1930s and spread globally. Moreover, negative selection sites were identified in the Stx2A proteins, and these sites were diffusely distributed throughout the protein. Two negative selection sites were located adjacent to an active site of the common Stx2A protein. Many conformational epitopes were also estimated in these proteins, while no conformational epitope was found adjacent to the active site. The results suggest that the stx2A gene has uniquely evolved and diverged over an extremely long time, resulting in many subtypes. The dominance of the strains belonging to Lineage 1 suggests that differences in virulence may be involved in the prosperity of the offspring. Furthermore, some subtypes of Stx2A proteins may be able to induce effective neutralizing antibodies against the proteins in humans.